1983
DOI: 10.1016/0141-1136(83)90003-x
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the Rates at which Oil from Natural Sources Enters the marine environment

Abstract: Previous estimates of the world-wide input of oil to the marine environment by natural seeps ranged from 0"2 to 6.0 million (metric)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Several reviews on this subject have been reported by Kvenvolden and co-workers. [83][84][85][86] Extensive research was performed by the ODP on the Blake Bahamas Ridge (between Bahamas Island and Cape Hatteras, North Carolina), [87][88][89] and other offshore locations as on Barklay Canyon out of Vancouver Island on the northern Cascadian Margin (Canadian Remotely Operated Platform for Ocean Science (ROPOS) project; Integrated Oceanic Drilling Project (IODP)), [90,91] at Bush Hill in the Green Canyon, [92][93][94] in the Mississippi Canyon of the Mexican Gulf, [95] on the southern summit of the Hydrate Ridge at the Oregon Margin, [94] and on the Håkon Mosby site in the Norwegian Sea. [95] More recently a successful exploration was tried on the Tigershark field in Alaminos Canyon in the Gulf of Mexico.…”
Section: Hydrates From Terrestrial and Oceanic Research And Drilling mentioning
confidence: 97%
“…Several reviews on this subject have been reported by Kvenvolden and co-workers. [83][84][85][86] Extensive research was performed by the ODP on the Blake Bahamas Ridge (between Bahamas Island and Cape Hatteras, North Carolina), [87][88][89] and other offshore locations as on Barklay Canyon out of Vancouver Island on the northern Cascadian Margin (Canadian Remotely Operated Platform for Ocean Science (ROPOS) project; Integrated Oceanic Drilling Project (IODP)), [90,91] at Bush Hill in the Green Canyon, [92][93][94] in the Mississippi Canyon of the Mexican Gulf, [95] on the southern summit of the Hydrate Ridge at the Oregon Margin, [94] and on the Håkon Mosby site in the Norwegian Sea. [95] More recently a successful exploration was tried on the Tigershark field in Alaminos Canyon in the Gulf of Mexico.…”
Section: Hydrates From Terrestrial and Oceanic Research And Drilling mentioning
confidence: 97%
“…For example, worldwide oil seepage is estimated to be 0.2 Million tonnes/year out of a total reservoir of 10 7 Mt (assuming 50 Myr residence time), or on the order of 10 -8 /year [5]. Although less is known about the ability of brine formations to retain buoyant gases, detailed site-specific studies and careful site selection can be used to identify sites with seepage rates that meet the performance requirements identified above.…”
Section: Discussionmentioning
confidence: 99%
“…Note that surface seepage is not necessarily equal to the rate at which CO 2 leaks from the primary storage reservoir, as the existence of stacked reservoirs [3,4] and natural seeps [5,6] demonstrates. Many subsurface processes such as solubility trapping, mineralization, diffusion, and residual gas trapping will attenuate the migration of CO 2 as it moves towards the land surface.…”
Section: Introductionmentioning
confidence: 99%
“…This approach involved broad assumptions based on considerations of the availability of CH 4 for seepage from all global geological sources through geologic time. The method used was adopted from previous work dealing with global estimates of crude oil seepage (Kvenvolden and Harbaugh, 1983;Miller, 1992). The total reservoir of CH 4 was estimated to be between 10 4 and 10 8 Tg and the half-life of this reservoir was set at 10 8 yr.…”
Section: Natural Macro-seepsmentioning
confidence: 99%